2016
DOI: 10.1107/s2059798315021609
|View full text |Cite
|
Sign up to set email alerts
|

Atomic resolution experimental phase information reveals extensive disorder and bound 2-methyl-2,4-pentanediol in Ca2+-calmodulin

Abstract: Calmodulin (CaM) is the primary calcium signaling protein in eukaryotes and has been extensively studied using various biophysical techniques. Prior crystal structures have noted the presence of ambiguous electron density in both hydrophobic binding pockets of Ca2+-CaM, but no assignment of these features has been made. In addition, Ca2+-CaM samples many conformational substates in the crystal and accurately modeling the full range of this functionally important disorder is challenging. In order to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Solvent assessable area was calculated using the pisa server and it was found that AtCaM7 structure has the highest solvent assessable area of 9868.5 Å 2 in comparison with other CaM, mentioned above. Recently it has been shown that MPD molecule is likely to favor more open conformations of the EF‐hands in the crystal of CaM . This could be the reason of having high solvent‐assessable area in case of AtCaM7.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent assessable area was calculated using the pisa server and it was found that AtCaM7 structure has the highest solvent assessable area of 9868.5 Å 2 in comparison with other CaM, mentioned above. Recently it has been shown that MPD molecule is likely to favor more open conformations of the EF‐hands in the crystal of CaM . This could be the reason of having high solvent‐assessable area in case of AtCaM7.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the total electrostatic force drives the ectodomain toward its binding partner indicating the dominant role of electrostatic forces in ectodomain homo-dimerization. Domain-domain interactions: this case illustrates the interdomain interactions of calmodulin in calcium loaded and peptide free state (PDB: 5E1K) (Lin et al, 2016). The total electrostatic force keeps the two lobes of calmodulin apart, thus helping it to retain the open conformational state of calcium loaded calmodulin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Monomeric structures of both Ca 2+ -bound CaM (holo-CaM) [28][29][30][31][32][33][34][35][36][37] and unbound CaM (apo-CaM) [38,39] have been studied experimentally. For example, X-ray crystallography and nuclear magnetic resonance (NMR) experiments have shown that CaM has two almost symmetrical globular domains; the domains are separated by a long linker region.…”
Section: Introductionmentioning
confidence: 99%
“…The linker region is disordered and flexibly connects the N-lobe and C-lobe, and then, the N-and C-lobe are expected to almost freely move independently from each other in the solution [38,39]. On the other hand, when Ca 2+ binds, the EFloop is pinched by Ca 2+ and the interaction between the entering-and exiting-helix of each EF-hand is inhibited, causing the helices to separate each other [28,29,[31][32][33][34][35][36][37]. This structural change exposes hydrophobic amino acids buried in the helix bundle, forming a hydrophobic pocket; the pocket is the binding site for the target protein [19,20].…”
Section: Introductionmentioning
confidence: 99%